PERAN CORE DAN HIDDEN CURRICULUM DALAM PEMBENTUKAN KEPRIBADIAN SISWA - Linda Yuliana; Muhajir Muhajir; Apud Apud (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
Core Curriculum is part of an integrated curriculum. Some of the characteristics learned from this curriculum are: This curriculum is planned on an ongoing basis, and will always be related, and is planned continuously. The core curriculum is structured in order to understand the direction of national education by taking into account the stages of student development and quality with regulations, national development desires, implementation and arts according to the type and level of each educational unit.This study was to determine the role of PAI's core and hidden curriculum in the formation of students' personalities, a case study at SMA Insan Kamil Tartila and SMA Al-Asmaniyah Tangerang district. This research method is a qualitative research with a case study approach with comparative analysis. The data collection techniques using interviews, observation and documentation. It can be concluded that the implementation of the core and hidden curriculum at SMA Insan Kamil Tartila and SMA Al-Asmaniyah both play a role in fulfilling all aspects seen from the value of strong faith, the value of worship with self-awareness carrying out obligations and leaving what is prohibited, moral values ​​with a commendable attitude. and carry out community service, and intellectual values ​​such as deepening literacy culture and skill values ​​such as liking to make Islamic short films, being proficient in leading tahlilan and memorizing corpses, all of which are to prepare students for the future so that they can achieve educational goals in accordance with the purpose of living useful in the world. and hereafter.